Global analysis of marine plastics and implications of control measure strategies - Yu, Ren-Shou; Yang, Ying-Fei; Singh, Sher (Frontiers in Marine Science, 2023)
Plastic pollution is a global environmental crisis that threatens marine ecosystems and human health. This study provides a comprehensive analysis of the current state of plastic pollution in oceans worldwide. We examined data on global plastic production, annual estimates of plastic emissions to oceans from different countries, surface plastic mass by ocean basin, the share of global plastic waste emitted to the ocean, the share of ocean plastics that come from the largest emitting rivers, microplastics in the surface ocean, and plastic mass and particles across the world surface ocean. Our analysis revealed alarming trends, such as the significant increase in plastic production since the 1950s and the projected estimate of up to 12,000 million metric tons of plastic waste in the natural environment by 2050. Additionally, we found that more than 1000 rivers account for 80% of global annual emissions, with Asia contributing the highest estimate of plastic emissions, followed by